THE EFFECTS OF EMPLOYEE EMPOWERMENT APPLICATIONS ON ORGANIZATIONAL CREATIVITY AND INNOVATIVENESS IN ENTERPRISESES: THE CASE OF OIZ - Celik, Adnan; Burhan CakÄ±ci, Ahmet; Celik, Neriman (European Scientific Journal, ESJ, 2014)
Experiencing change and intense competition in the business world,organizations need to adapt to changing conditions and generate new ideas tosubsist. This can only be achieved with a high proportion of organizationalcreativity in the enterprises. In this study, to increase productivity in recentyears, to manage change and to improve the performance of the staff are oneof the approaches that are used to improve the performance of personal,organizational creativity and innovation are examined. For this purpose,personal empowerment, organizational creativity and innovation with therelevant national and international studies were investigated, and theliterature is reviewed. Thereafter, an application was carried out in KonyaOrganized Industrial Zone (OIZ) on the staff.